Modified costotransverse approach combined with autologous iliac bone graft fusion and internal fixation in thoracic tuberculosis - Wei, Mengcheng; Zhang, Shishuang; Li, Qingbo; Cai, Lei; Zhou, Junlong; Liu, Weijun (Journal of orthopaedic surgery and research, 2025)
Due to the complexity of the thoracic spine's surrounding structures, thoracic tuberculosis surgery is challenging to perform, with difficult exposure, complex operations, numerous complications, and often unsatisfactory prognoses. Currently, it is believed that the posterior approach alone is superior to both the anterior and the combined anterior-posterior surgical methods in correcting spinal kyphosis and maintaining spinal stability. The posterior approach encompasses the transpedicular approach, costotransverse approach, and lateral thoracic approach. The aim of this study is to explore the clinical safety and efficacy of a modified costotransverse approach, originally known as 'banana peel preservation surgery,' combined with autogenous iliac bone graft fusion and internal fixation for the treatment of thoracic tuberculosis patients. From July 2016 to December 2024, 23 patients with thoracic tuberculosis were continuously treated using a modified costotransverse approach combined with autogenous iliac bone graft fusion and internal fixation. All patients were treated by the same surgical team, which also used other methods to perform surgeries on other patients (non-participants) during the study period. The group included 12 males and 11 females with an average age of 65.7 years. The duration of surgery, intraoperative blood loss, and visual analog scale (VAS) pain scores, Oswestry disability index (ODI) were recorded and analyzed before surgery, two weeks after surgery, and at the final follow-up. Neurological function was evaluated using the ASIA classification, and radiological results were assessed by measuring changes in the Cobb angle and the bone fusion status of the corrected fusion segment. The recorded surgical time for 23 patients ranged from 110 to 160 min (mean 133.7 ± 14.3 min), and blood loss ranged from 400 to 650 mL (mean 501.3 ± 74.9 mL). All incisions had healed by the first stage. The fusion time for the transplanted bone was between 3 and 7 months, with a median fusion time of 4 months. There was no loosening or breakage of internal fixation. At the final follow-up, C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) were both normal. Visual Analog Scale (VAS) and Oswestry Disability Index (ODI) scores showed significant improvement compared to preoperative values (P < 0.05). By the last follow-up, excluding patients who had normal neurological function previously, the remaining patients showed varying degrees of improvement in neurological function. The distribution of ASIA grades was as follows: 2 cases at grade C, 8 cases at grade D, and 13 cases at grade E. The average follow-up period for patients was 25 months, ranging from 13 to 36 months. Postoperative kyphosis did not progress significantly, and there was no recurrence of tuberculosis. In this group of 23 patients, the ASIA grade distribution at the last follow-up was 1 case at grade D and 22 cases at grade E, with a recovery rate of 90%. All patients received adequate decompression and bone grafting, leading to significant symptom improvement. There were no instances of pleural damage and all patients were free from symptomatic pleural effusion. The costotransverse process and the rib head provide sufficient surgical space of 1.1-2.1 cm to serve as decompression and bone graft channels. The preservation of the outer cortex of the rib can effectively prevent the risk of pleural injury and reduce the occurrence of pleural effusion. The modified costotransverse approach, "banana peel preservation surgery(Fig. 1)", combined with autologous iliac bone graft and internal fixation for the treatment of thoracic tuberculosis is a safe and effective surgical method for the treatment of thoracic tuberculosis.